Drop‐offs in the isoniazid preventive therapy cascade among children living with HIV in western Kenya, 2015–2019. Issue 8 (4th August 2022) - Onyango, Dickens Otieno; van der Sande, Marianne A. B.; Yuen, Courtney M.; Mecha, Jerphason; Matemo, Daniel; Oele, Elizabeth; Kinuthia, John; John‐Stewart, Grace; LaCourse, Sylvia M.
Abstract: Introduction: Isoniazid preventive therapy (IPT) can reduce the risk of tuberculosis (TB) in children living with HIV (CLHIV), but data on the outcomes of the IPT cascade in CLHIV are limited. Methods: We evaluated the IPT cascade among CLHIV aged <15 years and newly enrolled in HIV care in eight HIV clinics in western Kenya. Medical record data were abstracted from September 2015 through July 2019. We assessed the proportion of CLHIV completing TB symptom screening, IPT eligibility assessment, IPT initiation and completion. TB incidence rate was calculated stratified by IPT initiation and completion status. Risk factors for IPT non‐initiation and non‐completion were assessed using Poisson regression with generalized linear models. Results: Overall, 856 CLHIV were newly enrolled in HIV care, of whom 98% ([95% CI 97–99]; n = 841) underwent screening for TB symptoms and IPT eligibility. Of these, 13 (2%; 95% CI 1–3) were ineligible due to active TB and 828 (98%; 95% CI 97–99) were eligible. Five hundred and fifty‐nine (68%; 95% CI 64–71) of eligible CLHIV initiated IPT; median time to IPT initiation was 3.6 months (interquartile range [IQR] 0.5–10.2). Overall, 434 (78%; 95% CI 74–81) IPT initiators completed. Attending high‐volume HIV clinics (aRR = 2.82; 95% CI 1.20–6.62) was independently associated with IPT non‐initiation. IPT non‐initiation had a trend of being higher among those enrolled in the period 2017–2019 versus 2015–2016 (aRR = 1.91; 0.98–3.73) and those who were HIV virally non‐suppressed (aRR = 1.90; 95% CI 0.98–3.71). Being enrolled in 2017–2019 versus 2015–2016 (aRR = 1.40; 1.01–1.96) was independently associated with IPT non‐completion. By 24 months after IPT screening, TB incidence was four‐fold higher among eligible CLHIV who never initiated (8.1 per 1000 person years [PY]) compared to CLHIV who completed IPT (2.1 per 1000 PY; rate ratio [RR] = 3.85; 95% CI 1.08–17.15), with a similar trend among CLHIV who initiated but did not complete IPT (8.2/1000 PY; RR = 4.39; 95% CI 0.82–23.56). Conclusions: Despite high screening for eligibility, timely IPT initiation and completion were suboptimal among eligible CLHIV in this programmatic cohort. Targeted programmatic interventions are needed to address these drop‐offs from the IPT cascade by ensuring timely IPT initiation after ruling out active TB and enhancing completion of the 6‐month course to reduce TB in CLHIV.